Routine Assessment of Patient Index Data 3 (RAPID3) alone is insufficient to monitor disease activity in rheumatoid arthritis in clinical practice - Boone, Niels W. (2019)
There was no funding for this study. AS is supported by a doctoral grant from Fundação para a Ciência e Tecnologia (Foundation for Science and Technology) (SFRH/BD/108246/2015).